Epidemiology, clinical characteristics and potential mechanism of ibrutinib-induced ventricular arrhythmias - Pan, Yilin; Zhao, Yanan; Ren, Hangyu; Wang, Xintong; Liu, Caixia; Du, Beibei; Nanthakumar, Kumaraswamy; Yang, Ping (Frontiers in Pharmacology, 2024)
The Bruton's Tyrosine Kinase Inhibitor, ibrutinib, has been widely employed due to its significant efficacy in B-cell lymphoma. However, the subsequent cardiac complications, notably atrial fibrillation (AF) and ventricular arrhythmias (VAs) ,associated with ibrutinib treatment have emerged as a major concern in cardiooncology and hematology. Ibrutinib-induced AF has been well described, whereas mechanisms of ibrutinib-induced VAs are still under-investigation. The incidence of ibrutinib-induced VAs can vary vastly due to under-recognition and limitations of the retrospective studies. Recent investigations, including our previous work, have proposed several potential mechanisms contributing to this adverse event, necessitating further validation. The development of effective strategies for the prevention and treatment of ibrutinib-induced VAs still requires in-depth exploration. This review aims to establish a comprehensive framework encompassing the epidemiology, mechanistic insights, and clinical considerations related to ibrutinib-induced VAs. This article outlines potential strategies for the clinical management of patients undergoing ibrutinib therapy based on suggested mechanisms.